Penerapan Model Pembelajaran Project Based Learning Terhadap Kemampuan Berpikir Kreatif Siswa Kelas X Pada Mata Pelajaran Informatika di SMA N 2 Gorontalo - Yunus, Adinda putri; Suhada, Sitti; Ashari, Sri Ayu; Hadjaratie, Lillyan; Rohandi, Manda; Polin, Muchlis; Butsiarah, Butsiarah (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This research was motivated by the lack of creative thinking of students in informatics subjects. One of the factors that influences creative thinking is the lack of use of learning models. This research aims to determine the application of the Project Based Learning learning model. There is an increase in students' creative thinking abilities in class x informatics subjects at SMA N 2 Gorontalo. This research uses a quasi-experimental research method with a nonequivalent control group design, pretest posttest and observation. The samples for this research are class X-1 with a total of 31 students as the experimental class and class X-2 with a total of 31 students as the control class. The posttest in the experimental class had an average score of 80.16 and the average posttest score in the control class was 72.74, then the hypothesis test showed a significant 2 tailed value of 0.01<0.05. The observation results show that the aspect of students' creative thinking abilities, namely elaboration, reached 84% and an N-gain of 0.3960 was obtained in the medium category because students were able to complete projects according to schedule, so it can be concluded that there is an increase in creative thinking abilities by using the Project Based Learning model.Kata kunci: Model Project Based Learning, berpikir kreatif